TINJAUAN YURIDIS MENGENAI KEWENANGAN PENYIDIKAN DALAM TINDAK PIDANA KORUPSI - Kresna Wijaya, Pande Made; Suyatna, I Nyoman (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 03, Juli 2014)
Authority investigation into corruption cases under the laws applicable in Indonesia (Positive Law) has always been associated with law enforcement officers after police and attorney but an independent agency established specifically to handle corruption cases, namely the Corruption Eradication Commission (KPK), then investigative authority is shared also by KPK, so it is not uncommon conflict of interest between the law enforcement agencies in carrying out their respective duties. In this journal will discuss the investigative authority in corruption cases committed by KPK, the Police, and the Attorney.
Keywords: Authority of Investigation, Corruption